Fault analysis of a non-isolated three-level DC-DC converter integrated in a bipolar DC power grid - Oliveira, Cátia Patrícia Fraga (2022)
DC power grids present significant advantages over AC power grids, namely higher stability and controllability, and the absence of harmonic currents and reactive power. Moreover, DC grids facilitate the interface with renewable energy sources (RES) and energy storage systems (ESS). DC grids can be either unipolar or bipolar, where the latter consists of three wires and provides higher flexibility, reliability and transmission capacity. However, failures in bipolar DC grids (especially in the power semiconductors) can occur. The consequences of these failures can result in increased costs, depending on the damage, e.g., if it occurs a wire of the DC grid or in the connected power converter. Thus, in this paper is presented a fault analysis of a non-isolated three-level DC-DC converter used to interface solar photovoltaic (PV) panels into a bipolar DC power grid. The fault analysis is conceived through computational simulations, where can be observed the performance of the presented DC-DC converter under fault conditions in each wire of the bipolar DC grid. The simulation results demonstrate the DC-DC converter operating in two different situations: steady-state and transient-state. The control strategy applied in normal and fault conditions, as well as the different operation modes, are explained in detail.